Conversion disorder in a preschool age girl. (November 2016) - Bouras, Georgios; Michopoulos, Ioannis; Theofanopoulou, Nikoletta; Giannopoulou, Ioanna; Christodoulou, Christos; Dinopoulos, Argirios
This article reports a case of a 5-year-old girl with clinical manifestations of a conversion disorder. Children presenting with a conversion disorder very often have multiple investigations and more than two-thirds of them are admitted to the hospital. This case illustrates the necessity of adapting, from the outset, a multidisciplinary approach to diagnosis and management, which helps in providing an explanatory model that takes into account stressors, factors within the child and the family, and aids in planning an appropriate psychotherapeutic intervention based on the child's and family's needs.